Sustainable House For Low-Income Community In Indonesia - Wazir Z A (International Conference on Engineering and Technology Development (ICETD), 2017)
Efforts to eliminate slum areas in urban areas are a global program undertaken in many developed and developing countries through the provision of housing for Low Income Communities (MBR). In Indonesia, MBR house prices are limited to a maximum of IDR 200 million per unit, so developers effort to find ways to reduce costs to produce houses that meet the standards. This article reviews the house design for MBR which is not only cheap but qualifies for sustainability. The literature review resulted that this design should be able to accommodate a floor space of 10-13 m2 per capita as the optimum value of human social space. In addition, the results of the analysis require developers to provide a minimum green roof of 10% of the flat roof area, in order to lower the environmental temperature that affects the decrease of human aggressiveness and increase social attachment. Preferred materials were materials that were easy to obtain and cheap and certainly feasible to be building materials. Natural lighting during the day could be sunlight from closed glass windows and LED lights for night and enclosed spaces. Together with a number of other specifications, this article provided a concept of sustainable houses for MBR in urban environments that developers could use to reduce costs while ensuring sustainability. This concept refines the old concept that has been used by the government. The government needs to change standards and implement regulations that prohibit adding space or changing the shape of buildings. House prices with sustainable prototypes are slightly more expensive, but this is a compensation for unnecessary renovation while occupying the house